Playing the blame game: how attribution of responsibility impacts consumer attitudes toward plastic waste - Mayer, Monica; Kohl, Patrice (Frontiers in Communication, 2024)
Manufacturers often blame environmental issues on consumer behaviors. Plastic manufactures provide a classic example, engaging in marketing campaigns attributing responsibility for plastic waste to consumers and deflecting attention from the role of industry. Drawing on attribution theory, we conducted an experiment (n = 113) to test how messaging blaming consumers for plastic waste might influence attitudes, behavioral intentions, and policy support, compared to messaging blaming manufacturers. Compared with the manufacturer-blaming frame, the consumer-blaming frame resulted in less support for regulations increasing consumer accountability for plastic waste. We did not find a significant influence of the message frame on support for regulations holding manufacturers accountable for plastic waste. Based on these results, we suggest that practitioners consider framing messages surrounding plastic waste so as to minimize consumer blame in order to maximize potential support for plastic waste reduction initiatives.